Nonthermal processes and neutrino emission from the black hole GRO J0422+32 in a bursting state - Vieyro, Florencia Laura (2012)
Context. GRO J0422+32 is a member of the class of low-mass X-ray binaries (LMXBs). It was discovered during an outburst in 1992. During the entire episode a persistent power-law spectral component extending up to ∼1 MeV was observed, which suggests that nonthermal processes should have occurred in the system. Aims. We study relativistic particle interactions and the neutrino production in the corona of GRO J0422+32, and explain the behavior of GRO J0422+32 during its recorded flaring phase. Methods. We have developed a magnetized corona model to fit the spectrum of GRO J0422+32 during the low-hard state. We also estimate neutrino emission and study the detectability of neutrinos with 1 km 3 detectors, such as IceCube. Results. The short duration of the flares (∼hours) and an energy cutoff around a few TeV in the neutrino spectrum make neutrino detection difficult. There are, however, many factors that can enhance neutrino emission. Conclusions. The northern-sky coverage and full duty cycle of IceCube make it possible to detect neutrino bursts from objects of this kind through time-dependent analysis.